Gamified language learning: preserving regional dialects through interactive digital platforms: a case study of the Kelantanese dialect / Muhammad Alhakim Shafie … [et al.] - Shafie, Muhammad Alhakim; Che Fauzi, Ainul Azila; Mat, Asiah; Fauzi, Auni; Md Nasir, Syerina Azlin (Unit Penerbitan UiTM Kelantan, 2024)
The dynamic Kelantanese prioritise their dialect over anything else. It encourages regional traditions, mythologies, and historical narratives through song, dance, and drama. The dialect significantly influences Kelantanese social life, customs, and religion, providing speakers with a profound sense of identification and belonging. This distinctive cultural asset confronts significant difficulties. The Kelantanese dialect is under threat due to the younger generations’ transition to standard Malay and the absence of formal educational resources. The extensive use of media and communication technology generates apprehensions regarding linguistic uniformity, potentially undermining the Kelantanese dialect. To address these issues, this study focuses on the development and implementation of Dialect Master, a gamified web application designed to facilitate the learning of the Kelantanese dialect. By integrating engaging elements such as quizzes, progress tracking, and leaderboards, the application enhances user experience and learning outcomes. Technically, PostgreSQL was chosen for its reliability, with Drizzle ORM ensuring seamless database interactions and Next.js optimising server-side functionalities. Security was prioritised, resulting in the adoption of Clerk for authentication and encryption, thereby safeguarding data and enhancing user trust. Incentives such as points, badges, leaderboards, and quests were essential for prolonged engagement, while culturally pertinent content enhanced the relatability of the learning experience. The iterative development process employed agile methods incorporating AI-driven features, gamification aspects, and an intuitive user interface (UI), resulting in a dynamic tool for learning the Kelantanese dialect. The research highlights the advantages of gamification in education, illustrating how interactive components can enhance learner motivation and retention. Dialect Master emerges as a promising instrument for dialect acquisition, underscoring the significance of user-centered designs and gamified learning environments, with effective implementation and favorable user feedback accentuating its capacity to render the Kelantanese dialect enjoyable and accessible to learners.